THE EFFECT OF GENDER, MANAGERIAL OWNERSHIP, INTELLECTUAL PROPERTY OF THE BOARD OF DIRECTORS ON THE PERFORMANCE OF MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Sari, Selvi Yona; Sari, Desi Permata (Jurnal Apresiasi Ekonomi, 2023)
Abstract  This study aims to determine how much influence gender, managerial ownership and intellectual property of the board of directors has on the company's performance. The sample collection method used purposive sampling, with a total sample of 31 companies. The analytical method used is the classical assumption and multiple linear regression. The results obtained based on the Partial Test (t test) obtained: There is a negative and significant influence between gender on company performance, There is no positive and significant effect between managerial ownership on company performance, There is a positive and significant influence between intellectual property on company performance Then based on the test Simultaneous hypothesis (Test F) can be seen that there is a positive and significant influence between gender, managerial ownership and intellectual property together on company performance. Keywords: gender, managerial ownership, intellectual property of the board of directors and performance